Strain performance of tilapia in freshwater prawn polyculture (Journal of the Bangladesh Agricultural University, 2016)
Production performance of two tilapia (Oreochromis niloticus) strain viz. Chitralada and GIFT (Genetically Improved Farmed Tilapia) in fish-prawn polyculture system was compared, and possible effect of tilapia inclusion in freshwater prawn (Macrobrachium rosenbergii) culture was evaluated in 120 days of grow-out phase. There were three treatments, i.e. only freshwater prawn as control (T1), prawn + Chitralada (T2), and prawn + GIFT (T3) with three replications of each. Stocking densities for prawn juvenile was 30,000 ha-1 in all the treatments and for both tilapia strains were 10,000 ha-1. Floating feed containing 28% protein for tilapia and pelleted sinking feed for prawn were provided twice daily at a rate of 10-5% bw adjusted after each month of sampling. Water transparency was significantly lower (P